Intellectual property and intangible assets: Alternative valuation and financing approaches for the knowledge economy in Luxembourg - Tim Karius (European Institute for Knowledge & Value Management (EIKV), 2016)
With the disappearance of the bank secrecy and loss of e-commerce tax in year 2015, Luxembourg will be confronted to an existential challenge. Therefore, Luxembourgish economy has to reinvent itself and develop new key drivers boosting country's economic growth. Well known for the strong fund industry, Luxembourg needs alternative burst of growth to ensure long-term sustainability. An option could be innovation that arises from a knowledge-based economy. Intellectual property (IP) and intellectual capital (IC) driven companies like Amazon, SES or Netflix have market advantages, create jobs and drive innovation through the use and dissemination of new technology. However, a major problem for innovative companies, whose main enterprise value comprises identifiable or unidentifiable intangible assets, remains the funding. Specifically for Luxembourg, the funding solutions for those companies are very restricted. The trigger according to the funding problem for innovative companies consists in the absence of collaterals. At the lunch period, many OIP and IC driven companies have only small capital resources and their business value persist largely of intangibles. According to this initial situation, banks would today refuse the funding of this innovative business. During the last years, the main focus of the Luxembourgish government was the promotion of Luxembourg as an innovation hub such as the launch of Luxinnovation or the Cluster Initiative. Apart from the state aid program, they missed to consider IP and IC as an economic good that needs long-term support in order to create prospective values. Faced to the previously mentioned capital outflows due to the abandon of the bank secrecy, business of providing fund and consultancy to such innovative business could be a chance for Luxembourgish economy, thus refining their market and serving a very promising niche market. Identifiable or unidentifiable intangible possess and create a huge value and often outperform the value of tangible assets. Therefore an alternative valuation and funding approach in Luxembourg has to be developed. This master thesis deals with the problematic of determining a realistic value of company's intangibles that would give companies not only the access to alternative funding forms, but also to the classical bank loan.
Keywords: 330